A simple mixed finite element model for laminated glass beams. (15th June 2018) - Baraldi, Daniele
Abstract: A simple and effective beam finite element model is here proposed for studying the behaviour of elastic laminated glass beams made of two external glass layers connected by a polymeric thin interlayer, able to transmit only shear stresses. The finite element model is based on a mixed variational formulation, which assumes as independent fields the horizontal and vertical translations and transverse section rotations of both glass layers, together with interlayer shear stresses. Several numerical tests are performed showing the effectiveness of the proposed model and its convergence to the well-known upper (monolithic) and lower (layered) limits for a laminated glass beam.